Comportamento físico e hídrico de solos em interação com carvão vegetal - Santos, Emanuela Barbosa (2021)
The use of water retainers soil conditioners, such as biochar, has been increasingly studied in order to increase the efficiency of water use in agriculture in regions that are at risk of scarcity. However, there is still no consensus on what is the ideal/effective dose to be considered when using this conditioner and there is a gap in the sense of identifying the clay content from which the effects of the application of biochar are not perceptible. Thus, this work started from the hypotheses that: 1) changes in physical and water properties caused by biochar are greater in sandy soils; 2) there is a point in the regression graph of the biochar doses x change in soil properties, which defines the maximum effective dose; 3) soils containing more than 20% clay content are not noticeably modified in their physical and water properties when biochar is applied. Biochar was added in doses of 5, 10, 15, 20, 25, 30 and 35% (on a volume basis) in three soils: sand (with 1% clay), sandy loam (with 20% clay) and clay loam (with 30% clay). The samples were placed in PVC cylinders with 0.05 m in diameter and 0.05 m in height and taken to the incubation process for 90 days. After this period, the analyzes were carried out to obtain the variables: soil density, total porosity, macroporosity, microporosity, intrinsic air permeability, field capacity, permanent wilting point, water storage capacity and saturated hydraulic conductivity. The design used was completely randomized in a factorial scheme 3 (textural soil classes) x 7 (biochar doses) with 5 replications. Soils with a predominance of sand show more changes in physical and water properties in response to the application of biochar when compared to sandy loam and clayey loam soils, mainly related to water retention. The maximum dose, for most variables, was defined for the sandy loam soil at 20%, for the clayey loam soil at 25% and for the sand at 35% (maximum dose); that is, for sandy soil, the more biochar added, the greater the changes. The responses of soils with clay content greater than 20% (sandy loam and clayey loam) for the variables total porosity, intrinsic air permeability, available water capacity and hydraulic conductivity of saturated soil confirm this clay content value as a limiting factor to efficiency of this soil conditioner